The Relationship Between Husband's Support and Pregnant Women's Adherence to Antenatal Care Visits - Sri Wahyuni; Ria Wahyuni (PT. Nasyah Medika Care, 2024)
Background: Husband's support plays a crucial role in promoting maternal health behaviors, particularly adherence to antenatal care (ANC) visits, which are essential for preventing pregnancy-related complications and improving maternal and neonatal outcomes. However, inadequate family support remains a barrier to regular ANC utilization among pregnant women in Indonesia. Identifying the relationship between husband's support and adherence to ANC visits is important for developing family-centered maternal health interventions. Research Objective: This study aimed to determine the relationship between husband's support and pregnant women's adherence to antenatal care visits in Makassar City, Indonesia. Methods: This analytical observational study employed a cross-sectional design. A total of 31 pregnant women were recruited using a total sampling technique. Data on respondents' characteristics, husband's support (emotional, informational, instrumental, and appraisal support), and adherence to antenatal care visits were collected using a structured questionnaire. Data were analyzed using descriptive statistics and the Chi-square test with a significance level of p < 0.05. Results: Most respondents were aged 20–35 years (74.2%), had a high educational level (67.7%), and received good husband's support (64.5%). Furthermore, 67.7% of pregnant women adhered to the recommended antenatal care schedule. Bivariate analysis revealed a statistically significant relationship between husband's support and adherence to antenatal care visits (p = 0.001). Pregnant women who received good husband's support demonstrated a higher level of adherence to ANC visits than those who received poor support. Conclusion: Husband's support was significantly associated with pregnant women's adherence to antenatal care visits. Strengthening family-centered antenatal care through active husband involvement in maternal health education and counseling is essential to improve adherence to recommended ANC services and contribute to better maternal and neonatal health outcomes.